Harry Potter and the cursed child - Thorne, Jack (Harry Potter, 2016)
"As an overworked employee of the Ministry of Magic, a husband, and a father, Harry Potter struggles with a past that refuses to stay where it belongs while his youngest son, Albus, finds the weight of the family legacy difficult to bear"--OCLC.